PERMINTAAN MANGGA INDRAMAYU (Mangifera indica L) OLEH KONSUMEN DI PASAR TRADISIONAL PADA WILAYAH KOTA DI PROVINSI LAMPUNG - Deti Destiani; R Hanung Ismono; Rabiatul Adawiyah (Lampung University, 2015)
This research aimed to determine the consumption pattern and the influencing factors on the demand of indramayu mango by consumers in the traditional markets in Lampung’s urban areas. This research was conducted by survey method. The research was taken place in Bandar Lampung and Metro city purposively, at 12 traditional markets in Lampung urban areas by proportional method. The research respondents consisted of 84 consumers, chosen by accidental sampling. The data was collected in January to March 2015. The methods of the data analysis in this research were descriptive and quantitative. The descriptive analysis was used to determine the consumption pattern of indramayu mango. Quantitative analysis was used to determine the influencing factors on demand of indramayu mango by consumer in the traditional markets in Lampung’s urban areas. The result showed that the average consumption of indramayu mango was 58.83 gram per capita per day. The frequency of consumption was once every 1-2 days during mango season. The purpose of consumption was to meet the preference and the mango was consumed in fresh form or direct consumption. The influencing factors on the demand of indramayu mango by consumers in traditional markets in Lampung urban areas were the price of indramayu mango, household income, and family size. Key words: demand, indramayu mango, Lampung urban areas